Thermal aging rheological behavior of magnetorheological elastomers based on silicone rubber - Siti Aishah Abdul Aziz; Saiful Amri Mazlan; U Ubaidillah; Norzilawati Mohamad; Choi, Seung-Bok; Mohamad Amirul Che Aziz; Mohd Aidy Faizal Johari; Koji Homma (MDPI AG, Basel, Switzerland, 2020)
Engineering rubber composites have been widely used as main components in many fields including vehicle engineering and biomedical applications. However, when a rubber composite surface area is exposed to heat or sunlight and over a long-term accelerated exposure and lifecycle of test, the rubber becomes hard, thus influencing the mechanical and rheological behavior of the materials. Therefore, in this study, the deterioration of rheological characteristics particularly the phase shift angle (δ) of silicone rubber (SR) based magnetorheological elastomer (MRE) is investigated under the effect of thermal aging. SR-MRE with 60 wt% of CIPs is fabricated and subjected to a continuous temperature of 100 °C for 72 h. The characterization of SR-MRE before and after thermal aging related to hardness, micrograph, and rheological properties are characterized using low vacuum scanning electron microscopy (LV-SEM) and a rheometer, respectively. The results demonstrated that the morphological analysis has a rough surface and more voids occurred after the thermal aging. The hardness and the weight of the SR-MRE before and after thermal aging were slightly different. Nonetheless, the thermo-rheological results showed that the stress–strain behavior have changed the phase-shift angle (δ) of SR-MRE particularly at a high strain. Moreover, the complex mechanism of SR-MRE before and after thermal aging can be observed through the changes of the ‘in-rubber structure’ under rheological properties. Finally, the relationship between the phase-shift angle (δ) and the in-rubber structure due to thermal aging are discussed thoroughly which led to a better understanding of the thermo-rheological behavior of SR-MRE.